Utilizing Complex Systems Statistics for Historical and Archaeological Data - Lane, Justin E. (Journal of Cognitive Historiography, 2016)
This article examines two statistical tools useful for historians and archaeologists that are common in other fields, but rare in cognitive approaches to historical materials. These tools, network statistics and general linear modelling, have been utilized for decades in other disciplines in the cognitive sciences to test for complex and dynamic relationships between different variables. One of the strengths of these two approaches is that they can be used to draw statistical inference from complex, multivariate data; even when data is incomplete. This article outlines how these analyses work and when these approaches can be appropriately used to analyse historical and archaeological data.